Kekerasan Dalam Rumah Tangga dalam Perspektif Hukum Pidana - Muhammad Darwis; Iswandy Rani Saputra; Ali Ichsan Kiramang (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research was conducted with the aim of knowing the forms of domestic violence that are regulated in Law Number 23 of 2004 concerning Domestic Violence. And to find out the factors behind the occurrence of domestic violence in Parepare City throughout 2021-2022. The type of research used in this research is normative and empirical research or what is commonly known as legal research which combines the two. The research results show that forms of domestic violence are in the form of physical violence, namely beatings, kicking, and also encouragement by husbands to wives and also psychological violence that is carried out by saying words that should not be appropriate to say to a wife. These words can be in the form of dirty words, swearing and also speak using a high tone and it is more appropriate to say it by shouting at the wife. As well as the factors behind the occurrence of domestic violence in are individual factors, family factors. As well as community factors consisting of poverty.